PENGETAHUAN PERPAJAKAN, TRANSPARANSI DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Aritonang, Fri Yohana; Tipa, Handra (SCIENTIA JOURNAL, 2025)
This study is intended to evaluate and test the Influence of Tax Knowledge, Transparency and Quality of Tax Services on the Compliance of Individual Taxpayers at KPP Pratama Batam Selatan. The data analysis method uses quantitative in this study. The number of taxpayers registered at KPP Pratama Batam Selatan was recorded at 427,426 who became the population in this study. By using the slovin formula as a sampling technique. Using 100 respondents who are registered as taxpayers at KPP Pratama Batam Selatan. The data collection uses a questionnaire through a google form with measurements through a Likert scale.. Data processing using the SPSS version 26 program. This study provides the result that partially, Tax Knowledge has a positive and significant impact on taxpayer compliance. Transparency partially does not have a positive and significant impact on taxpayer compliance. And the Quality of Tax Services partially has a positive and significant impact on taxpayer compliance. Simultaneously, Tax Knowledge, Transparency and Quality of Tax Services have a positive and significant impact on the Compliance of Individual Taxpayers at KPP Pratama Batam Selatan.